Carbon-Based Modification Materials for Lithium-ion Battery Cathodes: Advances and Perspectives - Zhou, Luozeng; Yang, Hu; Han, Tingting; Song, Yuanzhe; Yang, Guiting; Li, Linsen (Frontiers in Chemistry, 2022)
Lithium-ion batteries (LIBs) have attracted great attentions as advanced power source and energy-storage device for years due to their high energy densities. With rapid growing demands for large reversible capacity, high safety, long-period stability of LIBs, more explorations have been focused on the development of high-performance cathode materials in recent decades. Carbon-based materials are one of the most promising cathode modification materials for LIBs due to its high electrical conductivity, high surface area and structural mechanical stability. This feature review systematically outlines the significant advances of carbon-based materials for LIBs. The commonly used synthetic methods and recent research advances of cathode materials with carbon coatings are firstly represented. Then the recent achievements and challenges of carbon-based materials in LiCoO2, LiNixCoyAl1-x-yO2, LiFePO4 cathode materials are summarized. In addition, the influence of different carbon-based nanostructures, including CNTs-based networks, graphene-based architectures on the performance of cathode materials is also discussed. Finally, we summarize the challenges and perspectives of carbon-based materials on the cathode materials design for LIBs.